2019
DOI: 10.1111/dmcn.14357
|View full text |Cite
|
Sign up to set email alerts
|

Primary stabbing headache in children and adolescents

Abstract: Aim To examine the characteristics of primary stabbing headache (PSH) in typically developing children and adolescents. Method In this prospective non‐interventional hospital‐based study, we examined 42 eligible individuals (24 females, 18 males; 26 white; mean age 12y 1mo, range 6y–16y 1mo) with spontaneous transient stabs. A headache focused history and/or a headache diary was obtained from each patient. All patients had normal neurological examination. Diagnosis of primary headache was based on the Internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…However, it is thought that the frequency of attacks is variable but, in general, they are low, with erratic intervals from daily to monthly. 7,22 In the largest population study for PSH, it was reported that 68% had stabbing headache frequencies of <1 stab/day. 23 We hypothesize that these groups with infrequent attacks could have a better chance of spontaneous remission of PSH, but future studies are needed to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is thought that the frequency of attacks is variable but, in general, they are low, with erratic intervals from daily to monthly. 7,22 In the largest population study for PSH, it was reported that 68% had stabbing headache frequencies of <1 stab/day. 23 We hypothesize that these groups with infrequent attacks could have a better chance of spontaneous remission of PSH, but future studies are needed to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the rare occurrence of PSH in children makes the study by Ahmed et al timely and useful. 3 The authors report on 42 children with a potential diagnosis of PSH and demonstrate the difficulties in assessment of clinical features and duration of attacks in particular: seven children reported attacks lasting less than 3 seconds, eight had attacks of more than 3 seconds and less than 2 minutes, and 27 patients had attacks lasting between 2 and 10 minutes. Until there are specific diagnostic tests for PSH, and indeed all other types of headache, clinical criteria will continue to be needed.…”
mentioning
confidence: 98%
“…Also, a category of probable PSH was introduced in the ICHD‐3 beta and ICHD‐3 which there is no requirement for a definite duration of the stabs if other conditions are fulfilled. Specific criteria for the diagnosis of PSH in children are lacking and studies on larger numbers of children and adolescents with PSH will help in making the diagnosis clearer …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor: Primary stabbing headache (PSH) is a type of headache disorder characterized by transient, sharp, stabbing pain within a localized area of the scalp, lasting only for a few seconds. Although the prevalence of PSH has been reported to range from 2.5% to 4.2% [1,2], epidemiological data on PSH are still insufficient. In our retrospective single-center study, 6 eligible individuals [1.5% 4 females and 2 males; mean age, 11 y and 8 mo (range, 8-14 y)] were observed among 400 patients with a profile of migraine (n = 353) and tension-type headaches (n = 162) with compounding conditions.…”
mentioning
confidence: 99%